ANALISIS KELAYAKAN MODUL PEMENTASAN MONOLOG BERBASIS KEARIFAN LOKAL DENGAN METODE ROLE PLAYING DAN TEKNIK 3M (MENIRU, MENGOLAH DAN MENGEMBANGKAN) - Hetilaniar, Hetilaniar; Murniviyanti, Liza (Universitas Muria Kudus, 2021)
The aim of this study was to describe the needs of monologue staging with the local wisdom base and 3M techniques (Imitating, Managing and Developong. The problem of the reasearch was at the need for a monologue staging module based on local wisdom with role playing method and 3M techniques this research was conducted in the Covid-19 situation that caused the students to learn independtly and online with the hope to materialize the learning in order to create the relevant support of learning drama to indonesian language education students, especially playing a role. The long term goal was to create the character literact students which were independent, creative and productive. This research resulted the monologue module staging on the base of local wisdom for the students of Indonesian language education PGRI University of Palembang that took drama theory and drama staging course. The measure the level of drama module course properness in order to support the students appreciation towards the drama